(3JfbjM GdJMbjb dGHf GdLhRis - (3GHf YHO GdgGOis; (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL,J (B597 (3g` s
(3ChdgG (B:s
(3jHJOF ef cJGH GdUjGe Edi BNQg hjJdhg JaSjQ HYV GdBjGJ s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B70 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdXGgQjI (B((3MOjK (B301) s
Keywords: (3GdMOjK h GdeUWdMs